Closure Techniques and Postoperative Outcomes of Major Lower Limb Amputation in Acute Limb Ischemia - Khadafy, Reza; Hapsari, Putie; Utomo, Hafidh Seno Radi (Faculty of Medicine, Universitas Padjadjaran, 2025)
Amputation, derived from the Latin